2002
DOI: 10.1128/mcb.22.12.4402-4418.2002
|View full text |Cite
|
Sign up to set email alerts
|

The G1 Cyclin Cln3 Promotes Cell Cycle Entry via the Transcription Factor Swi6

Abstract: In Saccharomyces cerevisiae (budding yeast), commitment to cell division in late G 1 is promoted by the G 1 cyclin Cln3 and its associated cyclin-dependent kinase, Cdc28. We show here that all known aspects of the function of Cln3 in G 1 phase, including control of cell size, pheromone sensitivity, cell cycle progress, and transcription, require the protein Swi6. Swi6 is a component of two related transcription factors, SBF and MBF, which are known to regulate many genes at the G 1 -S transition. The Cln3-Cdc2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 64 publications
(92 reference statements)
7
80
0
1
Order By: Relevance
“…Pramila et al (2006) showed that a Dhcm1 mutant spends longer in G 2 /M, consistent with our result (Table 1). Deletion of the G 1 transcription factors Swi4 (Gray et al 1997) and Swi6 (Wijnen et al 2002) have each been reported to result in an accumulation of cells in G 2 /M, which we also observed. In the case of the Dswi4 mutant, the G 2 /M phenotype is due to the fact the Dswi4 cells are defective in budding but not in DNA replication (Gray et al 1997).…”
Section: Resultssupporting
confidence: 75%
“…Pramila et al (2006) showed that a Dhcm1 mutant spends longer in G 2 /M, consistent with our result (Table 1). Deletion of the G 1 transcription factors Swi4 (Gray et al 1997) and Swi6 (Wijnen et al 2002) have each been reported to result in an accumulation of cells in G 2 /M, which we also observed. In the case of the Dswi4 mutant, the G 2 /M phenotype is due to the fact the Dswi4 cells are defective in budding but not in DNA replication (Gray et al 1997).…”
Section: Resultssupporting
confidence: 75%
“…Most likely, this is due to overexpressed Cln3 being able to target the Clb/Cdc28 inhibitor Sic1 for degradation. 41 In contrast to GAL-CLN3, induction of GAL-BCK2 gave rise to cell cycle entry both in the SWI6 and in the swi6Δ background. The swi6Δ strain behaved similarly to the SWI6 counterpart, as judged by flow cytometry and budding index measurements.…”
Section: Resultsmentioning
confidence: 99%
“…To control for non-specific expression changes we used a double deletion cln3Δ bck2Δ strain, again kept alive by MET3pCLN2. Cln3 function requires Swi6, 41 whereas Bck2's role in gene expression is at least partially independent of SBF and MBF. 42,43 To investigate further the Swi6 requirement for Bck2-and Cln3-mediated gene expression, we performed similar analyses in strains deleted for SWI6.…”
Section: Resultsmentioning
confidence: 99%
“…Checking the network, we found that at bistability k6 and k51 repress and activate Cdc20, respectively. From formal discussions and previous studies (26)(27)(28)(29), the presence of Cdc20 makes Cdh1 (Enemies) more active and represses CycB/CDK and cell exits miosis (G1 state again). This means that the system is inclined to be in the G1 state (monostable state) when Cdc20 increases, making the bistable state less stable.…”
Section: Analysis Of Sensitivitymentioning
confidence: 99%